2014
DOI: 10.1073/pnas.1407640111
|View full text |Cite
|
Sign up to set email alerts
|

Role of forkhead box protein A3 in age-associated metabolic decline

Abstract: Aging is associated with increased adiposity and diminished thermogenesis, but the critical transcription factors influencing these metabolic changes late in life are poorly understood. We recently demonstrated that the winged helix factor forkhead box protein A3 (Foxa3) regulates the expansion of visceral adipose tissue in high-fat diet regimens; however, whether Foxa3 also contributes to the increase in adiposity and the decrease in brown fat activity observed during the normal aging process is currently unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 41 publications
1
66
1
1
Order By: Relevance
“…Given that GCs previously have been reported to affect food intake in rodents (21, 22), we pair-fed the mice to exclude any confounding effects caused by the potential influence of GC on caloric intake. As previously described, 2-mo-old WT and Foxa3-null mice on a normal chow diet before treatment had comparable body weight, fat mass, and lean mass (29). Analysis of these metabolic parameters in mice after Dex treatment revealed that ablation of Foxa3 gave protection from the Dex-induced increase in fat mass and adipose tissue weight (Fig.…”
Section: Ablation Of Foxa3 In Mice Prevents Fat Depot Expansion Andsupporting
confidence: 63%
See 3 more Smart Citations
“…Given that GCs previously have been reported to affect food intake in rodents (21, 22), we pair-fed the mice to exclude any confounding effects caused by the potential influence of GC on caloric intake. As previously described, 2-mo-old WT and Foxa3-null mice on a normal chow diet before treatment had comparable body weight, fat mass, and lean mass (29). Analysis of these metabolic parameters in mice after Dex treatment revealed that ablation of Foxa3 gave protection from the Dex-induced increase in fat mass and adipose tissue weight (Fig.…”
Section: Ablation Of Foxa3 In Mice Prevents Fat Depot Expansion Andsupporting
confidence: 63%
“…WT and Foxa3-null mice (29) were kept in a humidity-and temperature-controlled environment on a 12-h light/dark cycle, with free access to chow diet and water. Mouse experiments were performed according to guidelines of the National Institute of Diabetes and Digestive and Kidney Diseases Animal Care and Use Committee and approved by the Institutional Animal Care and Use Committee of the National Institute of Diabetes and Digestive and Kidney Diseases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, we found differential methylation in Irs2 and Foxa 3, both of which are involved in insulin sensitivity (Ma et al ., 2014). While we see an increase in their expression in unexposed old animals, we do not see this increase in 6‐month‐old exposed animals.…”
Section: Discussionmentioning
confidence: 99%